PROFIL FITOKIMIA DAN KANDUNGAN METABOLIT BIOAKTIF PADA SARGASSUM PADA POLARITAS PELARUT BERBEDA - Muliawati Handayani; Nuning Mahmudah Noor; Pindo Witoko; Upy Raudatul Jannah (Jurnal Penelitian Pertanian Terapan, 2026)
Sargassum is recognized as a valuable source of bioactive secondary metabolites; however, quantitative comparisons of solvent-dependent extraction efficiencies remain limited. The present study rigorously assesses the extraction performance of methanol and hexane for phenolics, tannins, and major phytochemical constituents. Samples were subjected to seven-day maceration followed by phytochemical screening, determination of total phenolics using the Folin–Ciocalteu method, and quantification of total tannins with a tannic acid standard. Methanol exhibited a markedly higher extraction yield (4.23%) compared with hexane (1.13%). Furthermore, methanol extracts contained substantially greater levels of phenolics (16.13 mg GAE/g) and tannins (36.86 mg TAE/g) than those obtained with hexane, which yielded only 0.26 mg GAE/g and 0.42 mg TAE/g, respectively. The resulting phytochemical profiles highlight a clear polarity-driven selectivity, wherein methanol preferentially extracts polar metabolites, while hexane favors non-polar constituents. Collectively, these findings demonstrate that methanol is the superior solvent for obtaining Sargassum extracts enriched with bioactive compounds.